The ambivalence of the External Evaluation of Schools effects in the school practices - Gustavo E. Fischman; Amelia Marcetti Topper; Iveta Silova (Revista Educação Especial, 2018)
This article aims to describe the External Evaluation of Schools in Portugal through a brief framework of this system based on the guidelines of the European educational policies, in a logic of reciprocity between the national and transnational level, with the purpose of reflecting around the questions: Does the External Evaluation of Schools promote educational quality? What effects does the External Evaluation of Schools have on teaching practices? If, on the one hand, there are some studies that highlight the fact that the External Evaluation of Schools promotes a transformative and formative approach to the school practices through more or less direct consequences, on the other, there are studies that clarify that these effects reflected with shallow depth in the pedagogical reality. It is in this ambiguous context that is intended to deepen the reflection around the External Evaluation of Schools and their effects on school practices, namely, in the curricular and pedagogical dimensions, drawing on the conclusions of several national and international studies to increase the discussion.